Ø§Ù„Ø¥Ù„ØªØ¨Ù€Ø§Ø³ ÙÙ‰ Ù„ØºÙ€Ù€Ø© Ø§Ù„Ù‚Ù€Ø±Ø¢Ù† ÙˆØ¯ÙˆØ±Ù‡ ÙÙ‰ ØªØ¹Ù…ÙŠÙ€Ù…Ù€Ù€Ù€Ù‡ - Ridha, M. Rasyid (State Institute of Islamic Studies (IAIN) Palu, 2012)
Abstract: The Qurâ€™an is the guidance for all mankind. Therefore, the Arabic language used in the Qurâ€™an should be universal, and be easy to understand by all people. The Qurâ€™an has beautiful, fine and standard ambiguity. Because of the ambiguity of the Qurâ€™an language, almost all the words in the verses of the Qurâ€™an can be interpreted. The ambiguity is one of the semanticsÂ studies used in studying the meaning. The philosophers and the linguists employ three methods in studying the meaning, namely: 1) explaining the words naturally, 2) describing the sentences naturally, and 3) elaborating the meaning in the process of communication.Â Â Furthermore, to elaborate the meaning, one should view it from the aspects of word, of sentence, and of what the writer and the speaker need to communicate. All the processesÂ ofÂ meaning haveÂ Â been applied in the Qurâ€™an language in order toÂ be comprehended by people more easily.Kata Kunci : Ambiguitas, bahasa Arab, Alquran